Use of Drosophila as an Evaluation Method Reveals imp as a Candidate Gene for Type 2 Diabetes in Rat Locus Niddm22 - Kurenai Kawasaki; Sawaka Yamada; Koki Ogata; Yumiko Saito; Aiko Takahama; Takahisa Yamada; Kozo Matsumoto; Hiroyuki Kose (Journal of Diabetes Research)
Type 2 diabetes (T2D) is one of the most common human diseases. QTL analysis of the diabetic Otsuka Long-Evans Tokushima Fatty (OLETF) rats has identified numerous hyperglycemic loci. However, molecular characterization and/or gene identification largely remains to be elucidated due mostly to the weak genetic variances contributed by each locus. Here we utilized Drosophila melanogaster as a secondary model organism for functional evaluation of the candidate gene. We demonstrate that the tissue specific knockdown of a homologue of igf2bp2 RNA binding protein leads to increased sugar levels similar to that found in the OLETF rat. In the mutant, the expression of two of the insulin-like peptides encoded in the fly genome, dilp2 and dilp3, were found to be downregulated. Consistent with previous reports of dilp mutants, the imp mutant flies exhibited an extension of life span; in contrast, starvation tolerance was reduced. These results further reinforce the possibility that imp is involved in sugar metabolism by modulating insulin expression.